Cost-utility analysis of immune tolerance induction therapy versus on-demand treatment with recombinant factor VII for hemophilia A with high titer inhibitors in Iran - Rasekh HR; Imani A; Karimi M; Golestani M (Dove Medical Press, 2011)
Hamid Reza Rasekh1, Ali Imani1, Mehran Karimi2, Mina Golestani11Shahid Beheshti University of Medical Sciences, Department of Pharmaceutical Management and Pharmacoeconomics, School of Pharmacy, Tehran, 2University of Shiraz Medical Sciences, Hematology Research Center, Shiraz, IranBackground: In developing countries, the treatment of hemophilia patients with inhibitors is presently the most challenging and serious issue in hemophilia management, direct costs of clotting factor concentrates accounting for >98% of the highest economic burden absorbed for the health care of patients in this setting. In the setting of chronic diseases, cost-utility analysis, which takes into account the beneficial effects of a given treatment/health care intervention in terms of health-related quality of life, is likely to be the most appropriate approach.Objective: The aim of this study was to assess the incremental cost-effectiveness ratios of immune tolerance induction (ITI) therapy with plasma-derived factor VIII concentrates versus on-demand treatment with recombinant-activated FVIIa (rFVIIa) in hemophilia A with high titer inhibitors from an Iranian Ministry of Health perspective.Methods: This study was based on the study of Knight et al, which evaluated the cost-effectiveness ratios of different treatments for hemophilia A with high-responding inhibitors. To adapt Knight et al's results to the Iranian context, a few clinical parameters were varied, and cost data were replaced with the corresponding Iranian estimates of resource use. The time horizon of the analysis was 10 years. One-way sensitivity analyses were performed, varying the cost of the clotting factor, the drug dose, and the administration frequency, to test the robustness of the analysis.Results: Comparison of the incremental cost-effectiveness ratios between the three ITI protocols and the on-demand regimen with rFVIIa shows that all three ITI protocols dominate the on-demand regimen with rFVIIa. Between the ITI protocols the low-dose ITI protocol dominates both the Bonn ITI protocol and the Malmö ITI protocol and would be the preferred ITI protocol. All of the three ITI protocols dominate the on-demand strategy, as they have both a lower average lifetime cost and higher quality-adjusted life-years (QALYs) gained. The cost per QALY gained for the Bonn ITI protocol compared with the Malmö ITI protocol was $249,391.84. The cost per QALY gained for the Bonn ITI protocol compared with the low-dose ITI protocol was $842,307.69.Conclusion: The results of data derived from our study suggest that the low-dose ITI protocol may be a less expensive and/or more cost-effective option compared with on-demand first-line treatment with rFVIIa.Keywords: cost-utility analysis, immune tolerance induction, on-demand, rFVIIa